Acerca de la revolución capitalista de lo jurídico. Izquierda lacaniana y teoría crítica del derecho - Foa Torres, Jorge (2016)
This article proposes an approach to contemporary transformations of the legal, from the articulation between critical theory of law and the Lacanian left. On the one hand, it is stated that in contemporary times, under the dominance of the capitalist discourse, the legal has undergone a metamorphosis that can be characterized as the passage from bourgeois legal form to the right to jouissance. On the other hand, this paper claims that the law of populism can become, as residue of that discourse that it fails to reabsorb, a device capable of producing cuts on the capitalist circuit. In this context, the capitalist revolution refers to the radical change in policies and institutions and legal forms that lacks an emancipatory orientation and, on the contrary, promotes the consolidation and deepening of its repetition and reproduction. In this sense, identification with the subversive can become a mean by which the law of populism is capable of promoting the production of memories of terrorism that reinstate the social antagonism as a way of extracting a truth from the capitalist discourse for the return-invention of the political in its hegemonic form.